Shelter for women: Femina magazine cover design at pandemic situation - Fanny Lesmana; Asthararianty Asthararianty; Yeremia Ambat (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
Femina Magazine has a female with careers or work, both at home and in the public sphere as its audience target. Therefore, Femina Magazine has been publishing featuring cover designs for female models. However, in the May-June 2020 edition, Femina Magazine presents a different design concept. Femina did not use a female models as its cover but Femina is using illustrations for the cover. This closing design refers to the world situation affected by the Covid-19 pandemic outbreak. This study aims to determine the representation displayed by the cover design of Femina Magazine in the May-June 2020 edition. Research on the design of this magazine is based on design elements, namely picture, images and typography. The method used is Roland Barthes' semiotics, with a qualitative approach. The results showed that Femina Magazine has a different construction in presenting the cover design in the May-June 2020 edition. With this Covid-19 pandemic, Femina Magazine wants to show optimism for its readers in responding to this. The cover design for the May-June 2020 edition of Femina magazine also includes women having careers as a target for their readers to go to the domestic realm, namely returning home.